2018
DOI: 10.1016/j.meatsci.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile and carcass traits of feedlot Nellore cattle fed crude glycerin and virginiamycin

Abstract: Forty-eight bulls with an initial body weight (BW) of 408.4 ± 22.2 kg (age = 21 ± 2 months) were used in a randomized complete block design arranged in a 2 × 2 factorial design. The treatments were diets without virginiamycin (VM-) or with virginiamycin, at 25 mg/kg of dry matter (DM, VM+), and diets without crude glycerin (CG-) or with crude glycerin, at 100 g/kg DM (CG+). The cold carcass weight and cold carcass dressing (P ≤ 0.05) was greater in bulls fed crude glycerin diets. Total unsaturated fatty acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
7
0
2
Order By: Relevance
“…Nowadays, consumers are progressively conscious of the association that the consumption of some fatty acids is good for cardiovascular health. PUFA has a good effect on the health of humans, while on the health of humans, the SFA has adverse effects [51,52]. The present study’s results showed that appropriate amounts of BLTT linearly decreased the SFA and also MUFA, while they quadratically increased C18:3(n−3), these results are in agreements with Tan et al [9] who suggested that dietary addition of tea catechins could reduce the SFA and MUFA and also enhanced the content of C18:3(n−3) in meat of goat.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, consumers are progressively conscious of the association that the consumption of some fatty acids is good for cardiovascular health. PUFA has a good effect on the health of humans, while on the health of humans, the SFA has adverse effects [51,52]. The present study’s results showed that appropriate amounts of BLTT linearly decreased the SFA and also MUFA, while they quadratically increased C18:3(n−3), these results are in agreements with Tan et al [9] who suggested that dietary addition of tea catechins could reduce the SFA and MUFA and also enhanced the content of C18:3(n−3) in meat of goat.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the inclusion of lipid fodder in cattle diets can increase the beef content of beneficial fatty acids. Addition of dietary crude glycerol resulted in a 6.08% increase in unsaturated fatty acids in the meat of 22-month-old Nellore bulls (Castagnino et al, 2018). Based on this, future research should examine whether dietary lipid supplementation to Honghe yellow cattle can improve meat quality and taste according to human nutritional needs.…”
Section: Discussionmentioning
confidence: 98%
“…Montano et al (2015) reported increased weight gain (+ 3.3%) and feed e ciency (+ 12.0%) when crossbred (Brahman, Angus, Shorthorn and Charolais) were nished in feedlot and supplemented with steam-aked corn, distillers dried grains plus soluble and virginiamycin (26 mg/kg of DM) compared to bulls fed a control diet. Castagnino et al (2018) observed increased weight gain (+ 14%) and feed e ciency (+ 14%) in Nellore bulls supplemented with ground corn, soybean meal and virginiamycin (25 mg/kg of DM) compared to bulls fed a control diet. Virginiamycin alters rumen fermentation by increasing proportions of propionate, decreasing lactic acid, methane production and protein degradation .…”
Section: Introductionmentioning
confidence: 93%